Watermelon - Marr, Charles W.; Tisserat, Ned (My University, 2000)
This publication is for commercial vegetable production, specifically the production of watermelon in Kansas.
MF1107_2000_11
Keywords: MF1107; Crops; Fruits and Vegetables; MF